Draft Perspective Plan and Draft Fourth Five Year Plan of Himachal Pradesh - Planning Commission (Planning Commission, 1964)
Human planning is primarily for the own benefit of MAN. Man in Live and to Live well. And, since everything that begins just end, human life must also have its end. So it is not enough just to live well. When the end comes, man must end well too. Man is body, mind and soul. So, his life as also the end of his must be good in a bodily sense, in a mental and intellectual and in a spiritual sense.
Government of Himachal Pradesh